2019
DOI: 10.1002/slct.201803894
|View full text |Cite
|
Sign up to set email alerts
|

New Example of Metal‐Containing Monomers for Frontal Polymerization

Abstract: In the present work, new metal‐containing monomers based on copper(II) cinnamate (cinn), viz.: [Cu(cinn)2(bpy)(C2H5OH)], [Cu(cinn)2(phen)(H2O)2], and [Cu(cinn)2(tpy)(C2H5OH)2] (bpy = 2,2′‐bipyridine, phen=1,10‐phenanthroline and tpy=4′‐phenyl‐2,2′:6′,2′′‐terpyridine) were synthesized. At the first time, it was shown that these metal‐containing monomers undergo frontal polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We have previously shown [28][29][30][31][32][33][34][35] that the nature of the precursor has a significant impact on the main characteristics of the resulting nanomaterials. In particular, the introduction of long-chain hydrocarbon radicals into precursor molecules helps stabilize NPs and prevents their aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown [28][29][30][31][32][33][34][35] that the nature of the precursor has a significant impact on the main characteristics of the resulting nanomaterials. In particular, the introduction of long-chain hydrocarbon radicals into precursor molecules helps stabilize NPs and prevents their aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Frontal polymerisation is a fast and energy-efficient process in which a localised polymerisation zone is initiated and moves through the whole monomer formulation [21][22][23][24][25][26][27]. Recently, a process called radical-induced cationic frontal polymerisation (RICFP) has been developed for bubble-free bulk curing of epoxy resins [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nitrogen-metal-carbon (NMC) NPs obtained by thermolysis of precursors containing these elements have received wide attention due to their natural content, economic attractiveness and extended functionality. [23][24][25][26][27][28][29] Previous studies have shown that the activity of NÀ MÀ C catalysts largely correlates with the properties of precursors, thermolysis conditions, type of carbon, content of elements, etc. [30] Recently, Zhou et al synthesized an Fe/N co-doped graphitic carbon bulb with a high nitrogen content by pyrolysis of a Prussian blue precursor at a low temperature of 550°C.…”
Section: Introductionmentioning
confidence: 99%